PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS MODEL PEMBELAJARAN DISCOVERY LEARNING PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL KELAS VIII SMP - YULIA . (Departemen Matematika, 2021)
The purpose of this research is to to develop and produce learning tools in the form of valid and practical student worksheets on two-variable linear equation system material for grade VIII junior high school students by applying the Discovery Learning-based learning model. The model used is the Plomp development model which consists of three stages, namely the initial investigation phase, the development phase, and the assessment phase. The initial investigative phase consists of needs analysis, curriculum analysis, and concept analysis. In the development phase, self-evaluation, expert validation and individual evaluation are carried out. The practicality of the learning device is seen from the practicality questionnaire of students. Based on the results of data analysis, the validity and practicality shows that the Discovery Learning-based learning tools meet the valid criteria in terms of content and construct and are practical in terms of implementation, convenience and time required. So, it is concluded that the mathematics learning tool based on Discovery Learning on the material of the two-variable linear equation system for class VIII SMP that has been produced can be declared valid and practical. Keywords— Development Research, Discovery Learning, Mathematics